PENGARUH ATRIBUT PRODUK DAN LABEL HALAL SEBAGAI VARIABEL MODERATING TERHADAP KEPUTUSAN PEMBELIAN FACIAL WASH WARDAH - Devi Ilsanti; N. Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This study discusses product attributes and halal labels as moderating variables. The sample in this study was wardah facial cleansing consumers. To collect data by asking questions to customers who visit House Of Beauty Malang, to analyze data using validity test, reliability test, normality test, moderated regression analysis (MRA) and t test statistics, in the trial use SPSS Version 16.0. The results of the research product attributes significance to purchasing decisions, and halal labels proved as moderating variables the effect of attributes on purchasing decisionsKeywords: halal labels; product attributes; buying decision